Digital Literacy and Writing Proficiency: Integrating Networking Email in Higher Education for EFL Classroom - Saiful; Nur Qalby; Lusy Angraeni; Burhanuddin (Eduvelop: Journal of English Education and Development, 2025)
This research investigates the use of the Networking Email Strategy (NES) as a pedagogical tool to enhance writing skills among first‑semester Department of Public Administration students at Universitas Muhammadiyah Makassar (Unismuh Makassar) in the 2024/2025 academic year in an English as a Foreign Language (EFL) context. The objective is to examine the strategy's impact on five core writing components: content, organization, vocabulary, language use, and mechanics. A pre‑experimental, one‑group pretest–posttest design (N = 32) was applied involving pre-tests and post-tests over three instructional treatments using email writing tasks. Students engaged in real-time communication, received feedback, and revised their drafts through structured email exchanges. Results demonstrated a significant improvement in students' writing performance, with notable gains in vocabulary and organization. The post-test scores revealed that email-based writing fostered greater engagement, critical thinking, and grammatical accuracy. Students transitioned from informal, disorganized writing to more coherent, structured compositions. Findings align with literature suggesting that authentic writing contexts promote metacognitive development and linguistic competence. Additionally, the intervention supported digital literacy, empowering students to utilize technology responsibly for academic communication. This study provides empirical evidence supporting the integration of digital tools in language instruction, particularly in resource-limited educational settings. It suggests that email communication is a cost-effective, scalable strategy for improving both writing proficiency and digital skills. The implications are vital for educators seeking innovative methods to enhance student engagement and performance in EFL writing.